Contribuições da teoria histórico-cultural de Vigotski para a educação especial: análise do GT 15 da ANPEd - Würfel, Rudiane Ferrari (2015)
This study was developed in the line of research in Special Education Course for Master of Education in the Graduate Program of the Federal University of Santa Maria. The dissertation intended to contribute to the discussions which have arisen in the special education area, particularly in relation to contributions of Historical- Cultural Theory for this field, this research aims to examine how the theoretical framework of Vygotsky is allocated by the participating researchers GT 15 Special Education ANPEd and has the following objectives identify the major works of Vygotsky used in the research and map the prevalent themes in the papers presented at the GT 15 in the period from 1996 to 2013. The dissertation was constituted methodologically in a study bibliographical form, mixed qualitativequantitative method. To accommodate the demand of definition and organization of material, assumptions and research objectives specifically seek full papers published in the proceedings of the GT 15 Special Education ANPEd, which were based on the Historical-Cultural Theory of Lev SemionovichVygotsky, for both fall back on CD ROM called HISTORICAL MEMORIES ANPED: 30 YEARS (1996-1999) and for the years 2000-2013 researched in the ANPEd site. They selected 46 full papers that focused on the studies developed by Vygotsky. For interpretation of the results we used the method of Bardin Content Analysis, setting up five categories of analysis, which are: Development and Learning; Thought and Language; Play; Interaction and finally, Consciousness and Will. Research informed the Vigotskyan framework still seem to happen timidly in GT 15 Special Education ANPEd containing an average of three jobs per year, which shows hitherto little interest by the researchers of this GT theoretical basis for Historic-Cultural. However the contributions of selected research is valuable for further studies in the area.